KEGAGALAN KEBIJAKAN PEMERINTAH MEKSIKO MENGATASI KRISIS FEMINICIDE - Rohiman Mukti Mubarok; Linda Dwi Eriyanti; Muhammad Iqbal (Pusat Studi Gender Universitas Jember, 2021)
This study analyzes the causes of the failure of the feminicide prevention policy in Mexico. Even though the existence of women has been protected by law, they still experience forms of violence and these cases are increasing. So, the author aims to analyze why this policy failed in realizing protection for women. Based on the assumptions of socialist feminist theory and the concept of policy failure regarding the causes of policy failure and oppression against women due to the values and systems that have oppressed women. So, the failure of feminicide policies is caused by machismo as part of patriarchy and drug cartel business as a part of capitalism that oppresses women. A culture of machismo has influenced the increasing use of violence. Meanwhile, drug cartel businesses have resulted in an increase in criminal cases against women.